HUBUNGAN SPIRITUALITAS DENGAN BODY IMAGE PADA MAHASISWA WANITA - Ida Ayu Febiana (Program Studi Sarjana Ilmu Keperawatan dan Profesi Ners, Fakultas Kedokteran, Universitas Udayana, 2015)
Spirituality is how one views and respect themselves, others and the surrounding environment. Along with the changing of times, there is always a change in the trend of beauty that have an impact on changes in a person's perception of body image. In various studies that have been conducted on body image, the women is said to have the perception that tends to have negative body image than men. This research is a descriptive correlational with cross-sectional approach. The sampling technique is by simple random sampling with a sample size of 51 subjects research. Based on the results of statistical tests using Spearman's Rho is known that test. Sig = 0.000, thus Sig> 0.05. Thus the conclusion of this study is there was relationship between spirituality with body image on female students Semester VI Program A Nursing Science Faculty of Medicine, University of Udayana